Energy loss of 100 keV hydrogen isotopes in materials for nuclear applications - Petaccia, Mauricio Germán (2018)
This work studies the energy loss by different mechanisms in materials of nuclear interest (Al, Ti, Fe) when these are irradiated with an hydrogenic beam. The materials chosen were aluminum, titanium and iron, and the selected beam energy was of the order of 100 keV. The mechanisms considered for energy loss are electron excitation and phonon production, for both of them two quantities are defined: one to compare energy deposition by a single ion beam in different materials, the other to characterize several beams impinging a given material.